A gestão do modelo de negócios de empresas multinacionais de países emergentes - Calixto, Cyntia Vilasboas (2017)
Usually, one multinational enterprise deals with a portfolio of business models, since its foreign subsidiaries cannot just copy the headquarters’ model. Studies on the business model literature highlighted the complexity of this kind of organization, but they did not go further on their international operations. I’m aiming to understand what differs in those models around the globe and how the headquarters can cope with more than one business model by developing the ambidextrous capability. Thus, I’m looking forward to identifying some organizational elements as well as analyzing the network in the host country, which in juxtaposition, will determine the replication, renewal or even innovation of the original business model. In order to do that, I developed a theoretical framework and suggested some propositions based on the literature to evaluate the phenomena. The empirical setting was Brazilian Multinationals, composed by 40 interviews with executives of 17 different firms in both headquarters and their foreign subsidiaries. In addition, I triangulated the information with several types of secondary data, accounting to more than 300 documents. Then, selected four of them to analyze in depth through a multiple case study. The results had shown that multinational enterprises could use several tools to standardize some organizational procedures and share them by best practices through online systems and personal training. However, the host country environment (such as local institutions, staff and customers) stimulates several adaptations in their original model. Therefore, they created some separation mechanisms – spatial, temporal, and contextual - to be able to manage different business models concomitantly, trying to integrate the local culture in their business. Thus, this study contributes to the literature in two ways: (i) it brings to the international business’ perspective the analysis of the multinational’s business model, which can help us to improve our knowledge about the relationship between headquarters and foreign subsidiaries using a different lens; and (ii) in the business model literature, it explores the concept of business models’ portfolio and shows that the process of replication and renewal should be analyzed per foreign operation established by the company.